Effect of Scalability of Technology Deployment on Performance of Commercial Banks in Kenya - Mallit, Edmund Odiwuor; Karume, Simon, PhD; Mugo, Mary, PhD; Bowen, Daisy, PhD (Kabarak University, 2025)
Abstract Purpose of Study: This study examined the effect of the scalability of technology deployment on the performance of commercial banks in Kenya, guided by the Theory of Planned Behavior (TPB). Problem Statement: Despite Kenya’s leadership in digital banking, many commercial banks struggle to scale technologies effectively due to resource constraints, infrastructure gaps, and regulatory demands. This limits improvements in profitability, efficiency, and customer satisfaction, highlighting the need to examine how scalability and regulations affect bank performance. Methodology: The research adopted a qualitative content analysis approach, utilizing purposively selected secondary data sources such as policy documents, regulatory reports, industry reviews, and scholarly studies. TPB informed the analysis by linking organizational attitudes, perceived behavioral control, and normative pressures to the adoption and expansion of technological innovations. Result: The analysis revealed that scalability of technology deployment also has a positive relationship with the performance of commercial banks, although the effect is not statistically significant. Moreover, banks with limited capital or infrastructural constraints may struggle to scale their digital services effectively, limiting the observable impact on performance. Recommendation: Commercial banks should therefore invest in technologies and infrastructure that allow for future scalability. This includes modular IT systems that can be expanded as customer demand grows, cloud computing solutions that offer flexible data storage and processing, and digital service platforms that can be rolled out across multiple regions.
Full text
Keywords: Scalability; technology deployment; commercial bank performance; Theory of Planned Behavior; Kenya